A new divide? Assessing the transnational-nationalist dimension among political parties and the public across the EU. (June 2021) - Jackson, Daniel; Jolly, Seth
European politics is increasingly being contested along two dimensions: the economic left-right dimension and a relatively new dimension focused on European integration and immigration. We test this framework at the party and individual-levels in the European Union. First, we use the Chapel Hill Expert Survey to demonstrate that there is no simple relationship between these dimensions at the party level in many European Union countries, and in fact the two dimensions are increasingly orthogonal. We then use the 2019 European Elections Study to show that the transnational-nationalist dimension significantly improves vote choice models relative to models that ignore this dimension. Even more striking, the transnational-nationalist dimension is not just significant, but actually improves vote choice models as much or more than the economic left-right dimension.